Analisis Resiko Kecurangan terhadap Sistem Pengelolaan Dana Kapitasi Jaminan Kesehatan Nasional Di FKTP Pemerintah Kota Bitung - Soputan, Rocky; Tinangon, Jantje; Lambey, Linda (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2018)
Abstract. This study aims to analyze the risk of fraud against the National Healthcare Capitation Fund management system in Bitung City Government FKTP. The study is a qualitative research with case study approach. Data were obtained by conductngi in-depth interviews, observation, and documentation. The results showed that the risk of fraud management system capitation funds National Health Insurance Bitung City occurred. It is because of the weakness of JKN fund management system that is not compliant with regulations. It thus can disrupt health services. Additionally, the lack of internal control is due to the absence of supervision from the health department and Inspectorate offices, abnormality of the management of national health insurance capitation fund, and pressure from the work environment. The efforts to prevent fraud risk should be taken by establishing a structure of good control (supervision), especially the commitment of the head of health department followed by all employees included in FKTP level, applying Good Corporate Governance (GCG) with transparency principle in JKN capitation fund management and performing internal audit function.Keywords: fraud risk, system, JKN capitation fundsAbstrak. Penelitian ini bertujuan untuk menganalisis resiko kecurangan terhadap sistem pengelolaan dana Kapitasi Jaminan Kesehatan Nasional di FKTP Pemerintah Kota Bitung. Penelitian ini adalah penelitian kualitatif dengan pendekatan studi kasus. Data diperoleh melalui teknik wawancara mendalam, observasi dan studi dokumentasi. Hasil penelitian menunjukkan bahwa resiko kecurangan sistem pengelolaan dana kapitasi Jaminan Kesehatan Nasional di FKTP Pemerintah Kota Bitung terjadi karena lemahnya sistem pengelolaan dana kapitasi JKN yang tidak sesuai regulasi sehingga dapat menganggu pelayanan kesehatan, lemahnya pengendalian intern disebabkan tidak ada pengawasan dari Dinas Kesehatan dan Inspektorat, tidak normalnya pengelolaan dana kapitasi JKN, dan tekanan dari lingkungan kerja. Upaya menanggulangi resiko kecurangan harus dimulai dari membangun struktur pengendalian yang baik terutama komitmen Kepala Dinas diikuti oleh seluruh pegawai sampai ke tingkat FKTP, menerapkan Good Coorporate Governance (GCG) dengan prinsip transparansi dalam pengelolaan dana kapitasi JKN, dan menjalankan fungsi Internal AuditKata Kunci: Resiko kecurangan, sistem, dana kapitasi JKN